Censoring Music through Race: The struggle between African and Arab values and politics in the music of Zanzibar - Kirkegaard, Annemette (Danish Yearbook of Musicology, 2009)
Since the beginning of the popular musical style taarab in the eightteenth century, many instances of musical censorship have occurred. The diverse restrictions have often been related to the continued struggle between Arab and African values. Language, religion, singing style, instruments, and the inclusion of women have all been issues of great importance in the history of taarab. In this article I trace instances of the impact and effect of ethnic diversity and racism in taarab music in Zanzibar.